UPAYA INDONESIA UNTUK MENJADI ANGGOTA TIDAK TETAP DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA TAHUN 2019-2020 - Rahmiatin Tahdinata Maghfura; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain Indonesia's efforts in obtaining UN Security Council seats, describes the UN and the UN Security Council and discuss the interests of Indonesia became a non-permanent members of the United Nations Security Council. The author uses the theory of diplomacy in the frame of the liberal perspective and analysis of the level of the nation State. The method used is descriptive qualitative methods developed by way of research libraries. The discussion started with explaining the historically about the United Nations and UN Security Council which is one of the six main bodies of the United Nations. The UN Security Council has the task of maintaining international peace and security. Then proceed with the interests of Indonesia to become one of non-permanent members of the United Nations Security Council. After it analyzes the efforts Indonesia became a member of non-permanent members of the United Nations Security Council period 2019-2020. The results of this research concluded that the success of Indonesia became a member of the UN Security Council is efforts through a multitrack diplomacy strategy. With the jargon of The True Partner for World Peace Indonesia that compete with Maldives could won a member seat at the UN Security Council. This is not just a triumph of soft power, but it also provides an invaluable opportunity for Indonesia to achieve the national interests, world peace and security as well as enhancing his reputation.            Keywords: Indonesia, The UN Security Council, The National Interest